2021
DOI: 10.1111/cyt.12995
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 RNA may rarely be present in a uterine cervix LBC sample at the asymptomatic early stage of COVID 19 disease

Abstract: Objective Currently, it is thought that uterine cervix mucosal samples present a low risk of SARS‐CoV‐2 exposure. So far, there is no evidence of SARS‐CoV‐2 detection in Papanicolaou (Pap) smears. Nevertheless, clinicians could be exposed unaware to the coronavirus while performing and handling a Pap smear. We aimed to retrospectively evaluate the presence of SARS‐CoV‐2 RNA in cervical liquid‐based cytology (LBC) samples in women who tested positive for a nasopharyngeal COVID‐19 PCR test. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In another case, the virus was identified in a 26-year-old female patient, but with a low viral load, both in the cervical sample and in the nasopharyngeal swab, thus, it was assumed that the patient was at an asymptomatic early stage. This data suggests that cervical samples had a low risk of exposure to SARS-CoV-2, even during the viral incubation period after a positive nasopharyngeal test [12].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In another case, the virus was identified in a 26-year-old female patient, but with a low viral load, both in the cervical sample and in the nasopharyngeal swab, thus, it was assumed that the patient was at an asymptomatic early stage. This data suggests that cervical samples had a low risk of exposure to SARS-CoV-2, even during the viral incubation period after a positive nasopharyngeal test [12].…”
Section: Discussionmentioning
confidence: 69%
“…SARS-CoV-2 RNA may rarely be present in a uterine cervix LBC sample at the asymptomatic early stage of COVID 19 disease [12].…”
Section: /Czech Republicmentioning
confidence: 98%
“…Thirty-one studies (20 cohort, 6 cross-sectional and 5 case series) assessed the presence of SARS-CoV-2 in vaginal secretion of 859 patients (875 specimens). Eight studies reported SARS-CoV-2 detection in 23 patients 31–38. Information on viral persistence was reported by only two studies (8 and 13 days) 35 36.…”
Section: Resultsmentioning
confidence: 99%
“…Hypoxia may antagonize the iron transporter which causes abnormal iron metabolism, and then leads to ferroptosis (Naidu et al 2023 ). It is reported that hypoxia induced by COVID-19 may increase the ferritin in circulation and cause iron deficiency which cause the occurrence of oxidative stress and lipid peroxidation, resulting in ferroptosis (Lechuga et al 2021 ; Ondic et al 2021 ; Suresh et al 2021 ; Wang et al 2021b ). Pneumonia is the primary caused by COVID-19.…”
Section: Ferroptosis and Hypoxic Diseasesmentioning
confidence: 99%